Discussion on the evolution of architecture of the core network of cellular Internet of things - Hongyuan MA; Wei ZHOU; Yan FU; Yongping SHAO; Dan LI (Dianxin kexue)
At present, there are two Internet of things networks facing 2G, 4G, NB-IoT and facing toB core networks.In order to simplify the network, enhance the capability, enhance the benefit, and facilitate the operation and maintenance, it is necessary to define the target architecture of 5G-oriented Internet of things core network.Based on the existing network problems and combined with the driving force of network evolution, the network evolution target structure, evolution strategy and service solution were analyzed and discussed.It provides a reference for operators to plan and construct the Internet of things.